Law and finance: Common-law and civil-law countries compared - Michael Graff (ETH Zurich, KOF Swiss Economic Institute, 2005)
The law and finance theory is an ambitious and fascinating attempt to combine insights from the theory of corporate finance, institutional economics, legal and economic history as well as the recent studies on the determinants of economic growth into an encompassing theory, thereby filling important gaps of our understanding of the ultimate causes and linkages underlying modern economic development. It argues that the legal system, which today's countries inherited from the past, is crucial in the way it is favouring - or hampering - financial development. The major conclusion of this literature is that the common law system generally provided the more favourable basis for financial development and economic growth, and on the other hand, the French branch of the civil law tradition is the least favourable in this respect. This paper identifies a number of problems that cast serious doubt on the soundness of the empirical basis generally referred to in this literature. However, our analyses support the idea that the legal tradition has pronounced effects with respect to shareholder protection. In particular, while a critical look at the indicators revealed that there is not much evidence that common law countries protect financial investors better than civil law countries, we find support for the view that investors are treated differently.
Keywords: K22; G20; P00; 330; Gesellschaftsrecht; Wirtschaftswachstum; Vergleich; Rechtsökonomik; Rechtsordnung